DANGEROUS DRIVER’S BEHAVIOR - Libor Topol; Ivo Drahotský (Acta Polytechnica CTU Proceedings)
Different types of dangerous driver’s behavior are discussed in this paper. Case study analysis of young drivers’ hazardous behavior is also provided from authors’ practices. The practical research is collaborated with the statistical data that aggressive driving induces the number of fatalities on the roads in the Czech Republic by 25%. The improvement to driver’s training and other countermeasures is then suggested.